Spectral Assignments and Reference Data - Zhou, S.; Yang, J.; Liu, F.; Tu, P.
Two novel unsaturated E-ring pentacyclic triterpenoid saponins, ilexhainanoside A and ilexhainanoside B, were isolated from the leaves of Ilex hainanensis. Their chemical structures were determined by MS, NMR spectroscopy and chemical analysis. Complete assignments of the 1H and 13C NMR spectroscopic data were achieved by 1D and 2D NMR experiments (HSQC, HMBC, ROESY and 1H-1H COSY).
Keywords: NMR; 1HNMR; 13C NMR; 1D NMR; 2D NMR; ILEX HAINANENSIS; TRITERPENOID SAPONIN; ILEXHAINANOSIDE A; ILEXHAINANOSIDE B